(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2017)
تمّت دراسة الخصائص الطيفيّة لمعقدات الحديد الثلاثي مع حمض اللّبن بطريقة طيفيّة فوتومتريّة. وجرى البحث في ستوكيومتريّة (تركيبة) المعقّد الفعّال ضوئيّاً المتشكّل في الجملة: ، ضمن شروط تجريبيّة محدّدة؛ تتراوح فيها التراكيز الابتدائيّة لكلّ من الحديد الثلاثيّ وحمض اللبن ما بين: ، كما تتغيّر قيمة - الوسط ضمن المجال: . أظهرت الدراسة أن نسبة الحديد الثّلاثي إلى حمض اللّبن في المعقد الفعّال ضوئيّاً (الأكثر قدرةً على امتصاص الضوء وتأثّراً به) هي ؛ أي أنّ صيغة هذا المعقد هي: . دُرست امتصاصيّة المعقد الفعّال ضوئياً عند أطوالٍ موجيّة مختلفة ، وتبيّن أنّه يُبدي امتصاصاً أعظميّاً عند طول الموجة . حُسبت القيمة التقريبيّة لمعامل الامتصاص الموليّ لهذا المعقد فبلغت: ≈ ، والقيمة التقريبيّة لثابت تفكّكه فبلغت . اقتُرحت آليّة أوّلية لتفاعل التحطّم الضوئيّ للمعقّد ، بما يتوافق مع الدراسات المرجعيّة السابقة . وهذه الآلية المقترحة تعتمد على العلاقة بين الامتصاصيّة وحركيّة التفاعل الضوئيّ، وليس على التحليل الكيفي والكمّي لنواتج التفاعل. The spectral characteristics of the iron(III) lactate complexes were examined by the spectrophotometric methode, and the absorbance of these complexes has been studied at diferente wavelengthes . The stoichiometry of the photoreactive complex formed in the iron(III)-lactate system has been investigated in aqeuous solution under determinative experimental conditions. Initial concentrations whether of Iron(III) or of lactic acid ranged from to , and -values were belonging to the range . The results showed, that the ratio of iron(III) to lactate in the photoreactive complex is 1:2, i.e. its formula is . This complex has a maximum absorption at 365 nm. Its molecular absorption coefficient is about ≈ and its dissociation constant is about . The tentative mechanism for the photochemical decomposition of the complex has been suggested, in agreement with the reference studys . The suggested mechanism depends on the relationship between the absorbance and the photoreaction kinetics, and it is not based on the qualitative or quantitative analysis of reaction products.